2018
DOI: 10.4103/aer.aer_54_18
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of dexmedetomidine and clonidine as an adjuvant to intrathecal bupivacaine in lower abdominal surgeries

Abstract: Context:Spinal block is the first choice for lower abdominal surgeries. Bupivacaine is the most common local anesthetic used but has a shorter duration of action. Many adjuvants have been used to improve the quality of analgesia till postoperative period. In this study, we used α2-agonists.Aims:The aim of this study is to compare the effects of intrathecal dexmedetomidine and clonidine as adjuvants to hyperbaric bupivacaine with respect to onset and duration of sensory and motor blockade duration of analgesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Accumulating data suggest that intravenous dexmedetomidine selectively prolonged the duration of sensory block without prolonging motor block, whereas perineural or intrathecal dexmedetomidine significantly prolonged the duration of motor block [ 19 ]. Another study showed that intravenous dexmedetomidine prolonged motor block as well as sensory block in spinal anesthesia, but the prolongation of motor block was less than that of sensory block [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data suggest that intravenous dexmedetomidine selectively prolonged the duration of sensory block without prolonging motor block, whereas perineural or intrathecal dexmedetomidine significantly prolonged the duration of motor block [ 19 ]. Another study showed that intravenous dexmedetomidine prolonged motor block as well as sensory block in spinal anesthesia, but the prolongation of motor block was less than that of sensory block [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Duration of sensory blockade, defined in most studies as the time taken for the sensory blockade to regress to the S1 dermatome, was significantly longer in the DEX group in 15 out of 19 studies (Attri et al, 2015;Gupta et al, 2011;Kataria et al, 2018;Li et al, 2015;Mahendru et al, 2013;Munnoli et al, 2016;Naaz et al, 2016;Patro et al, 2016;Rahimzadeh et al, 2018;Ramaiah et al, 2015;Rao et al, 2015;Solanki et al, 2013;Sun et al, 2015;Suthar et al, 2015;Yektaş & Belli, 2014). Total duration of motor blockade, defined in most studies as the time taken for complete motor recovery (Bromage score 0), was significantly longer in the DEX group in 11 out of 21 studies (Attri et al, 2015;Ganesh & Krishnamurthy, 2018;Kataria et al, 2018;Mahendru et al, 2013;Munnoli et al, 2016;Patro et al, 2016;Rahimzadeh et al, 2018;Rao et al, 2015;Solanki et al, 2013;Suthar et al, 2015;Yektaş & Belli, 2014).…”
Section: Block Characteristicsmentioning
confidence: 97%
“…The majority of studies used loss of pinprick sensation and the Bromage scale to assess sensory and motor blockade, respectively. Time to onset of sensory block, defined in most studies as the time taken from intrathecal injection to loss of sensation at the T10 dermatome, was significantly faster in the DEX group in eight out of the twenty studies that reported this outcome (Attri et al, 2015;Ganesh & Krishnamurthy, 2018;Gautam et al, 2018;Kataria et al, 2018;Li et al, 2015;Naaz et al, 2016;Patro et al, 2016;Ramaiah et al, 2015). Onset of motor blockade, defined mostly as the time taken to reach a Bromage score of 3, was significantly faster in the DEX group in seven out of 18 studies (Attri et al, Patro et al, 2016;Ramaiah et al, 2015;Suthar et al, 2015).…”
Section: Block Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations